THE STRATEGY OF MADRASAH PRINCIPALS IN BUILDING EFFECTIVE LEADERSHIP TO IMPROVE TEACHER PERFORMANCE AT STATE ISLAMIC JUNIOR HIGH SCHOOLS IN PADANGSIDIMPUAN CITY - Subuh Waldo Huakbar; Anhar Anhar; Zainal Efendi Hasibuan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This background is based on the importance of the effective leadership role of madrasah principals in improving teacher performance, particularly at Padangsidimpuan State Islamic Junior High School. Challenges such as lack of teacher motivation, minimal professional training, and suboptimal communication between leaders and staff are factors that hinder performance improvement. Therefore, adaptive and innovative leadership strategies are needed to create a conducive work environment and encourage improvements in the quality of education. Methodology: This research uses a descriptive qualitative approach with data collection methods through participant observation, in-depth interviews, and documentation studies at MTsN 1, MTsN 2, and MTsN Preparatory State Islamic Junior High School 3. Padangsidimpuan. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results of this study showed that the madrasah principal implemented eight main strategies in building effective leadership to improve teacher performance; (1). Coaching strategy, through training, individual mentoring, and Professional Learning Community (PLC). (2). Supervision strategy, based on participatory academic supervision and constructive feedback. (3). Motivation strategy, through verbal appreciation, emotional support, and professional development. (4). Reward strategy in the form of certificates, incentives, and additional task trust. (5). Discipline strengthening strategy with a systemic, restorative approach, and based on a collective work culture. (6). Family gathering strategy to build emotional bonds and social capital in the madrasah environment. (7). Structured academic supervision strategy through a cycle Collaborative planning, observation, and reflection. (8) Lesson Study strategy as a vehicle for developing distributive leadership and improving the quality of learning. Effective leadership of madrasah principals is built through a holistic approach that integrates administrative, pedagogical, and relational aspects. The implemented strategy has proven significant in improving teacher performance through increased competence, motivation, collaboration, and a positive work culture. This study recommends the need to strengthen teacher development programs and leadership training based on Islamic values for the sustainable improvement of educational quality in madrasahs.